ALSO and BLSO evaluation Thailand Myanmar border - McGready, R; Rijken, M J (University of Oxford, 2021)
This data was collected over 13 years (2008-2020) as part of ongoing evaluation of adult education in a resource limited setting on the Thailand Myanmar border. The data is in excel. The excel file has a worksheet of data and a worksheet that provides a key to the data. The questionnaire sheet is also included in the package.